Widening access to veterinary education: descriptive analysis of ethnicity, societal representation and educational background of applicants to veterinary education in Aotearoa New Zealand. Issue 3 (24th March 2021) - Jillings, EKP; Curtis, E; Gardner, D; Parkinson, TJ; Hecker, KG; Cogger, N
ABSTRACT: Aims: To describe the ethnicity of domestic applicants for selection into the professional phase of veterinary education in Aotearoa New Zealand from 2003 to 2019, and to compare this with the ethnic composition of New Zealand society. This study also aims to explore whether there are differences in the demographic features and educational background of Māori applicants compared to non-Māori applicants that may be relevant to widening access to veterinary education. Methods: This study was conducted with a Kaupapa Māori research methodology. Data for all applicants to the Bachelor of Veterinary Science programme at Massey University (Palmerston North, NZ) from 2003 to 2019 were retrieved from the university's Student Management System and the School of Veterinary Science selection application databases. Self-identified ethnicity was analysed in four time periods (2003–2006, 2007–2012, 2013–2016, 2017–2019) defined by factors that might influence whether an individual chose to apply for selection into the veterinary programme. Gender, age, previous university experience, decile and type of high school, and being first in family to attend university were compared between Māori and non-Māori. Results: From 2003 to 2019, 3, 819 individuals submitted 4, 802 applications for selection into the veterinary programme. Across all time periods, applicants who identified as Māori (274/4, 802; 5.7%) or Pacific (56/4, 802; 1.2%) were underrepresented compared to the New Zealand population (Māori 16.5%; Pacific 8.1%), while applicants who identified as European (4, 035/4, 802; 84%) were over-represented (70.2% of the New Zealand population). The proportion of Māori (p = 0.82) and Pacific (p = 0.31) applicants did not change over time, while the proportion of European applicants decreased from 853/968 (88.1%) to 823/977 (84.2%; p < 0.001). Compared to non-Māori, Māori applicants were more likely to have attended a lower decile school (p < 0.001), have attended a state rather than private or overseas school (p = 0.003) and to have been the first in their family to attend university (p = 0.001). Conclusions: Māori are underrepresented in the veterinary applicant pool and veterinary profession in comparison to the New Zealand population. Additionally, Māori applicants differed from non-Māori applicants in pre-university factors that are barriers to university attendance. Implementing activities and processes aimed at widening veterinary programme access with the eventual goal of improving the ethnic representation of the veterinary workforce needs to be a priority for the university and profession.